IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH INDEX CARD MATCH STRATEGY - Ayu Farida; Evie Kareviati (PROJECT (Professional Journal of English Education), 2021)
English is one of the subjects studied by Indonesia students' ranging from Junior High School until University. One aspect that plays an important role in learning English is vocabulary mastery. For that reason, the purpose of this study is to know whether or not there is any improvement of vocabulary mastery by using an index card match strategy. This research was conducted at SMPN 4 Cikalongwetan using the classroom action research (CAR) method with 30 students as samples. Learning using the index card match itself is considered to be able to increase vocabulary mastery as an impact of interesting and exciting learning, it can be seen from the score of post-test which is higher than the pre-test score, with a pre-test score of 64.66, post-test score cycle 1 of 79.33 and post-test score cycle-2 of 83,66. This means the index card match strategy is effective to improve students' vocabulary mastery. Keywords:  Vocabulary, Index Card Match, CAR